Within-child associations between sleep quality and emotional self-regulation over 6 months among preschool-aged (3- to 5-year-old) children - Godzik, Cassandra M.; Carlson, Delaina D.; Pashchenko, Oleksandra I.; Ballarino, Grace A.; Emond, Jennifer A. (Frontiers in Sleep, 2024)
Objective: We leveraged an observational, repeated-measures study to examine the within-child associations between sleep quality and emotional self-regulation, controlling for between-child effects.: Children aged 3-to-5-years-old and one parent each were recruited from the community in Northern New England for a 6-month study on child media use, 2019-2022. Parents completed online surveys at baseline and 2-, 4-, and 6-months post-baseline. Child sleep quality was measured with the validated Children's Sleep Habits Questionnaire (CSHQ) modified for preschoolers; higher scores indicate worse sleep quality (range 32-96). Child emotional self-regulation was measured with the validated Child Social Behavior Questionnaire (CSBQ); higher scores indicate better emotional self-regulation (range 1-7). Adjusted mixed effects linear regression was used to model the associations between nighttime sleep quality (exposure) and emotional self-regulation (outcome) measured at each of the four study time points while disaggregating the between-and within-child effects.Results: Children (n=91) were largely white, non-Hispanic (88.7%) and from a higher socialeconomic status. Sleep quality scores averaged 38.9 (SD: 6.6) at baseline; 23.1% of children had scores >41, which is considered evidence of significant sleep problems. Emotional Emotional self-regulation scores averaged 4.2 (SD: 1.0). There was a significant within-child association between sleep quality and emotional self-regulation. Specifically, aA decrease in sleep quality at any one timepoint, relative to each child's own mean sleep quality, related to worse emotional self-regulation (standardized beta, βs = -0.31; 95% CI: -0.53, -0.09); the between-child effect was not significant. Results were consistent when limited to children with complete data at all study visits (n=78). Conclusions: Findings support a causal, within-child association between sleep quality and emotional self-regulation in preschool-age children, with effects evident over 6-months.